2005
DOI: 10.1111/j.1365-2699.2005.01345.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of history in explaining diversity patterns in tropical riverine fish

Abstract: Aim Documentation of the ongoing effect of rain forest refuges at the last glacial maximum (LGM) on patterns of tropical freshwater fish diversity.Location Tropical South and Central America, and West Africa. MethodsLGM rain forest regions and species richness by drainage were compiled from published data. GIS mapping was applied to compile drainage area and contemporary primary productivity. We used multiple regression analyses, applied separately for Tropical South America, Central America and West Africa, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
2
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 52 publications
8
69
2
4
Order By: Relevance
“…In contrast, the presence of high mountains in the region is likely to have buffered fishes from past climate-change events by maintaining flows through cloud capture, especially in small streams. This hypothesis is consistent with the work of Tedesco et al (2005) who found the highest fish species richness in Central and South American and West African drainages that were connected to rainforest refugia during the last glacial maximum. Increases in the basal elevation of orographic cloud formation of 100 m per degree of warming are predicted, with major implications for flow volumes in upland tropical streams (Still et al 1999).…”
Section: Wet Tropicssupporting
confidence: 81%
“…In contrast, the presence of high mountains in the region is likely to have buffered fishes from past climate-change events by maintaining flows through cloud capture, especially in small streams. This hypothesis is consistent with the work of Tedesco et al (2005) who found the highest fish species richness in Central and South American and West African drainages that were connected to rainforest refugia during the last glacial maximum. Increases in the basal elevation of orographic cloud formation of 100 m per degree of warming are predicted, with major implications for flow volumes in upland tropical streams (Still et al 1999).…”
Section: Wet Tropicssupporting
confidence: 81%
“…Our dataset was restricted within a very narrow latitudinal range (less than 10°), implying little or no affect of cline gradient and productivity (also related to latitude) on species occurrence (Tedesco et al 2005). Furthermore, as both seasonal and less seasonal drainages occur in northern and southern parts of our study area (LĂ©vĂȘque and Paugy 1999), latitudinal gradient could not have produced the observed patterns of demographic strategies or any unwanted spatial correlation in the analyses.…”
Section: Spatially Related Factorsmentioning
confidence: 90%
“…For instance, the West African rivers that currently display relatively more stable hydrological conditions are those located in historically stable regions (i.e., Pleistocene refuges; Dupont et al 2000). These rivers tend also to have higher species richness (when river size has been accounted for), and higher historical hydrological stability that could have allowed the speciation and/or the persistence of a higher proportion of equilibrium species (Tedesco et al 2005).…”
Section: Historical Issuesmentioning
confidence: 98%
“…Variations in species composition, structure and distribution in fish assemblages has been attributed to area (i.e. basin area, lake surface area), regional net primary production, habitat heterogeneity (Tedesco, Oberdorff, Lasso, Zapata, & Hugueny, 2005), substrate type, microhabitat type and water flow (Mendonça et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Variations in species composition, structure and distribution in fish assemblages has been attributed to area (i.e. basin area, lake surface area), regional net primary production, habitat heterogeneity (Tedesco, Oberdorff, Lasso, Zapata, & Hugueny, 2005), substrate type, microhabitat type and water flow (Mendonça et al, 2005).Land use plays a key role in shaping the environment on global, regional and local scales (Krusche et al, 2005). Changes in the type of land cover influence the biodiversity and ecosystem services (Foley et al, 2007), global climate (Hartmann et al, 2013), biogeochemical cycles and water cycles (Laudon et al, 2016).…”
mentioning
confidence: 99%